Star Wars battlefront : twilight Company - Freed, Alexander (Del Rey, an imprint of Random House, 2015)
Twilight Company (men and women, human and nonhuman--of the Sixty-First Mobile Infantry) gives the Rebel Alliance's hardest-fighting warriors a crucial chance to turn retreat into resurgence as they strike at the ultimate target: the very heart of the Empire's military machine.